Fibroblast encapsulation in gelatin methacryloyl (GelMA) versus collagen hydrogel as substrates for oral mucosa tissue engineering - Fahimeh Tabatabaei; Keyvan Moharamzadeh; Lobat Tayebi (Elsevier, 2020)
Purpose: Over the past decades, a variety of biomaterials have been investigated in terms of their suitability for oral mucosa tissue engineering. The aim of this study was to compare collagen and GelMA hydrogels as connective tissue scaffolds for fibroblasts and as substrates for seeding and culture of oral epithelial keratinocyte cells. Methods: Human primary oral fibroblast and keratinocyte cells were isolated from gingival biopsies. The mixture of fibroblasts with GelMA or collagen gel were aliquoted within six-well tissue culture plate inserts and cross-linked using visible light or reconstitution buffer/heat, respectively. The viability of fibroblasts in the hydrogels was investigated after one and three days of cultivation using the PrestoBlue assay. Following the addition and culture of oral keratinocytes onto the connective tissue constructs, the tissue-engineered oral mucosa was assessed histologically. Results: The tissue viability assay shows that collagen hydrogels encapsulating fibroblasts displayed significantly higher cell viability than cell-laden GelMA constructs after 24 and 72 h (p < 0.05). A stratified and differentiated epithelium has formed on the surface of cell-laden collagen hydrogel but not on the surface of the GelMA-based substrate. Conclusion: Collagen-based scaffold offers superior biological properties compared to GelMA hydrogel in terms of oral fibroblast growth, as well as epithelial cell adhesion and differentiation. Therefore, collagen-based hydrogels remain the preferred choice for oral mucosa tissue engineering.